P204 Barriers and facilitators to delivering latent tuberculosis infection (LTBI) screening and treatment to recent migrants: a survey of providers in a high prevalence TB setting in the UK. (12th November 2019) - Ikram, S; O'Brien, K; Rahman, A; Potter, J; Burman, M; Kunst, H
Abstract : Introduction and objectives: Screening and treatment of migrants to the UK for LTBI is a key component of the TB collaborative strategy in England. The London borough of Newham is a pilot site for the national programme whereby care is delivered entirely within primary care. We sought to identify facilitators and barriers to delivery of care by understanding the views of healthcare professionals delivering the programme. Methods: Between August 2017 and February 2018, questionnaires were sent to all GP practices and community pharmacies in the LTBI programme. Healthcare assistants (HCAs), Practice Nurses (PNs), GPs and community pharmacists were asked to complete questions about potential facilitators and barriers, and their role in service delivery. Results: 15 GPs, 17 HCA/PNs and 11 pharmacists completed the questionnaires. The relationship of patients with primary care staff was the most commonly considered facilitator across all professional groups. However the barriers differed – GPs listed time to see patients as the common barrier; pharmacists, HCAs and PNs listed patient understanding about LTBI as the most common barrier (see table 1). Role specific feedback: Pharmacists believed themselves as best placed to check patient adherence to LTBI medication (11/11), and pill count was believed to be the best measure of adherence (9/11). Almost all pharmacists (10/11) stated they had found good adherence to medication. Most GPs (10/15) also believed pharmacists were best placed to monitor medication adherence and GPs additionally believed comprehensive counselling used in their first consultation improved adherence. HCAs/PNs found explaining why an IGRA test was needed as the most challenging part of their role (8/15). On a 5-point Likert scale, GPs (mean=4.33/5) and pharmacists (mean=5.00/5) both agreed that LTBI care should be provided in primary care. However, most GPs (mean 4.25/5) felt pressurised to deliver too many services in primary care, compared to pharmacists who disagreed with this statement (mean=2.00/5). Conclusion: In a primary care based model of care for LTBI screening and treatment in migrants, healthcare professionals felt ease of access and patient relationships were the key facilitators to care. GPs but not other professionals expressed pressure on services as a major barrier.